Липська пізньопалеолітична культура: аналіз та інтерпретація джерел - Ситник, О.С. (Кам’яна доба України, 2010)
У статті подаються результати історіографічного та інтерпретаційного аналізу літературних джерел і окремих фондових колекцій памяток Волині, з якими повязують термін липська палеолітична культура, запропонований Г.Григор’євим та М.Островським у 1966 р. Автор не вважає цей термін адекватним і науково обґрунтованим, оскільки ним об’єднують різнокультурні матеріали, що зібрані на поверхні і розкопані стаціонарно. Scientific works, above all those belong to G. Grigor’ev and M. Ostrovs’kyi (1966), G. Grigor’ev (1970),
V. P’iasets’kyi (1999) are analyzed in proposed article. Mentioned works are dedicated to the hypothesis of
existence and division into periods of original Paleolithic “Lyps’ka archaeological culture” in Volhynian region.
Historiography and interpretation analysis of literary sources and separate collections of finds (Lypa I,
Myrogoshcha, Nobel’) is given in relation to this term and concept.
Most of sites, which were initially attributed to this culture, have not stratigraphy, and their archaeological
materials are collected on the ground and generally assorted. Collections of basic sites of Lypa I and Lypa
VI, excavated by V. Savych are still not analyzed, not studied and not published in a sufficient measure.
Most sites explored by V. Piyasets’kyi, and attributed by him to Lyps’ka culture do not have clear stratigraphy,
absolute dates and satisfactory scientific argumentation. They belong to different cultures within the range
of Late Paleolithic traditions.
Therefore the author considers this term inadequate and scientifically not advisable, especially for
periodization constructions of Volhynian Paleolithic.